2019
DOI: 10.1002/jcb.29453
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐598 acts as an inhibitor in retinoblastoma through targeting E2F1 and regulating AKT pathway

Abstract: Recently, microRNAs (miRNAs) receive more attention due to their role in the pathogenesis of malignancies. Retinoblastoma (RB) is the most serious and harmful malignant tumor in infants and young children with eye diseases, which often endangers the lives of children. This study was designed to determine how miR-598 is involved in RB progression. In this study, quantitative reverse transcription-polymerase chain reaction, Western blot, dual-luciferase reporter, Cell Counting Kit-8, and Transwell assays were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…MiR‐320a, miR‐383, and miR‐598 have been described as having a tumor suppressor role, being negatively regulated in several malignant tumors. In tumors of the lung, stomach, liver, colorectal, pancreas, bone marrow, prostate, esophagus, testis, bones, ovarium, breast, pancreas, central nervous system, and head and neck, overexpression of these miRNAs led to several suppressive features including inhibition of proliferation, migration, invasion, and metastasis; induced apoptosis; improved prognosis and sensitivity to chemotherapy 37–66 . In our study, we observed an increase CN for the genes miR‐320a, miR‐383, and miR‐598 in PA, while residual PA and CXPA displayed a decrease in CN, showing a potential tumor suppressor function, consistent with existing literature findings.…”
Section: Discussionsupporting
confidence: 48%
“…MiR‐320a, miR‐383, and miR‐598 have been described as having a tumor suppressor role, being negatively regulated in several malignant tumors. In tumors of the lung, stomach, liver, colorectal, pancreas, bone marrow, prostate, esophagus, testis, bones, ovarium, breast, pancreas, central nervous system, and head and neck, overexpression of these miRNAs led to several suppressive features including inhibition of proliferation, migration, invasion, and metastasis; induced apoptosis; improved prognosis and sensitivity to chemotherapy 37–66 . In our study, we observed an increase CN for the genes miR‐320a, miR‐383, and miR‐598 in PA, while residual PA and CXPA displayed a decrease in CN, showing a potential tumor suppressor function, consistent with existing literature findings.…”
Section: Discussionsupporting
confidence: 48%
“…Abnormal overexpression of E2F1 has also been reported in glioma (16,38). Interestingly, there has been increasing attention that miRNAs post-transcriptionally regulate E2F1 expression, including miR-205-5p, miR-342-3p, miR-93, and miR-598 (39)(40)(41). To better comprehend the tumor-suppressive function of miR-1258 mechanistically, we identified E2F1 as one of the direct and functional targets for miR-1258 in GBM.…”
Section: Discussionmentioning
confidence: 98%
“…Existing studies have found that miRNAs play a significant role in various biological processes, including cell apoptosis. 29,30 Furthermore, miRNAs have diagnostic and therapeutic value in many fields, such as tumor suppression, inflammation, 30,31 For example, in prostate cancer cells, miR-1972 targeted the miRNAs LIM and SH3 protein 1 (LASP1) and negatively regulated its expression, while upregulating miR-1972 inhibited cell proliferation, migration, invasion, and tumor formation and enhanced apoptosis. 32 In stroke-induced immunodeficiency syndrome, the increased expression of miR-4443 induced monocyte dysfunction by targeting tumor necrosis factor receptor-associated factor 4 (TRAF4), which may function as a crucial mediator, but in Graves' disease, this process induces CD4+ T cell dysfunction by targeting TRAF4.…”
Section: Discussionmentioning
confidence: 99%